Pengaruh CAR, LDR, Ukuran Dewan Komisaris Independen, dan Ukuran Dewan Direksi Terhadap Kinerja Bank Umum - Ika Centika; Diyan Lestari (UNIVERSITAS KALBIS, 2023)
This research aims to analyze the effect of capital adequacy ratio, loan to deposit ratio, board of independence commissioners’ size, and board of directors’ size on the performance of conventional commercial banks in Indonesia. Performance of conventional commercial banks is proxied by net interest margin. Purposive sampling technique is used as a sample technique. Researcher determined 48 conventional commercial banks has fulfilled the sample criteria for data analysis in this research. This research uses panel data regression with fixed effect model approach to analyze the data. The results show that CAR, LDR, and board of independence commissioners’ size affect the bank performance. While board of directors’ size has no effect on bank performance. Variable CAR, LDR, board of independence commissioners’ size, and board of directors’ size represent of bank performance by 77.18%.